Evaluation of policy for granting of rock mining business license in Palu Donggala axis road - Djambar Djambar; Saiful Darman; Abdul Rifai (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study evaluates the implementation effectiveness of the Rock Mining Business License (IUP) policy in Palu City and Donggala Regency, Central Sulawesi. The focus lies on the extent to which the implementation aligns with good mining practices and its socio-environmental impacts. Despite the strategic value of the Palu–Donggala area, the policy has led to significant issues, including non-compliance by IUP holders, weak administrative oversight, and minimal contributions to community welfare. Some companies operate beyond their licensed areas and neglect environmental standards, resulting in increased pollution and deteriorating public health. Data were collected through interviews with key stakeholders, including government officials, company representatives, and impacted communities. The analysis employed the model developed by Miles, Huberman, and Saldana, consisting of data condensation, display, and conclusion drawing. The findings show that in terms of input, companies have not invested adequately in human resource development, and the infrastructure at mining sites remains poor. Regarding the process, operational practices often deviate from applicable regulations, and supervisory mechanisms are weak. The output dimension reveals that negative impacts such as pollution, infrastructure degradation, and low absorption of local labor outweigh the perceived benefits to surrounding communities. In the outcome dimension, the policy tends to generate adverse effects on both the environment and people’s lives, leading to negative perceptions among affected residents. In conclusion, the implementation of the rock mining license policy in the Palu–Donggala area has not met expectations and requires urgent policy reform and enforcement to ensure alignment with regulatory standards, environmental sustainability, and equitable community outcomes.